Bismuth niobate-based pyrochlore phase high-entropy ceramic and single-phase preparation method thereof
By introducing five equimolar magnetic transition metal elements into the bismuth niobate-based cocochloride phase, NbO7-δ was prepared by sol-gel combustion method (Nb0.36Bi1.64) (Fe0.2Co0.2Ni0.2Mn0.2Cr0.2)NbO7-δ High-entropy ceramics solve the problems of single-phase preparation and insufficient magnetic properties near room temperature, and realize the magneto-optical and high-temperature resistance of bismuth niobate-based cocochlorite phase.
Patent Information
- Application Number
- CN202411438748.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The prior art is difficult to achieve single-phase preparation and near-room temperature magnetism in the bismuth niobate-based cocochlorite phase, resulting in insufficient magnetic properties of the material and the inability to achieve magneto-optical and electrical versatility.
Using the chemical formula of (Nb0.36Bi1.64) (Fe0.2Co0.2Ni0.2Mn0.2Cr0.2)NbO7-δ, the niobic acid with ferromagnetic and magnetoelectric polyferrous properties was prepared by the improved sol-gel combustion method. Bismuth-based cocochlorite-phase high-entropy ceramics use five equimolar magnetic transition metal elements to coexist in the bismuth niobate-based structure, induced complex magnetic interactions.
It has successfully achieved room temperature ferromagnetic and magnetoelectric multiferrometry, has good wide-spectral light absorption characteristics, and maintains a stable cocoaluminite cubic crystal phase structure at a high temperature of 1000℃. It has magneto-optical and multifunctionality, suitable for magneto-electric sensor parts, Optoelectronic devices and other fields.
Smart Images

Figure CN119320275A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of multifunctional high-entropy ceramics, and in particular relates to bismuth niobate-based pyrochlore phase high-entropy ceramics and a single-phase preparation method thereof. Background Art
[0002] A2B2O7-type oxides are usually classified into two categories: fluorite structure and pyrochlore structure. Because their crystal structure has high tolerance and can accommodate the coexistence of multiple types of components, they can have multiple functions such as electricity, magnetism, optics and catalysis in a single phase. Therefore, they can be regarded as a candidate material system for the discovery of important high-entropy ceramics. At present, the high-entropy research of this type of material is mainly focused on the RE2Zr2O7 (RE is a rare earth element) system. By using the high-entropy design of A-site rare earth elements, low thermal conductivity can be achieved, which can be applied to thermal barrier environment coatings. It can also induce relaxor ferroelectric behavior and achieve ultra-high dielectric energy storage density. For detailed research progress, please refer to the review Recent Progress and Current Challenges of High-entropy A2B2O7-type Oxides[J], Journal of Xinyang Normal University(Natural Science Edition), 2023, 36(4): 679-683.
[0003] Niobium-bismuth-based A2B2O 7-δ In recent years, the type of oxide has gradually attracted attention. Its structure is a cubic defect pyrochlore phase structure, and its chemical formula is Bi 2-M Nb 2+M O6O′, the specific structure has the following three characteristics: approximately bismuth atomic positions in the stoichiometric ratio M are occupied by niobium atoms to form positional disorder; there are a large number of unoccupied oxygen vacancies; there are vacancy defects at the positions of oxygen atoms and bismuth atoms. Such a special structure can easily accommodate many disordered arrangements, showing the flexibility of atomic arrangement, but its crystal structure is very stable, so it is very suitable for multi-component high-entropy design. Pyrochlore phase bismuth niobate itself has excellent dielectric and optical properties, which are attributed to the 6s orbital electron pairs of its bismuth atoms, and the hybridization of 2p empty orbitals with oxygen atomic orbitals, and is also affected by complex multi-type defects. If magnetism is introduced, the material can have multifunctional properties such as magneto-optical and photoelectric properties. It belongs to the category of advanced functional materials and has great application prospects. However, studies have found that single or double magnetic atom doping cannot excite the magnetism of the material, let alone achieve near-room temperature magnetism, such as reported in the literature. 1.647 (Fe 1-y Co y ) 1.157 Nb 1.118The magnetic transition temperature of O7 (0≤y≤0.5) single-phase ceramics is only 7-9K, and it has no magnetism near room temperature (J.Mater.Chem.C, 2019, 7, 1263).
[0004] It can be seen that in pyrochlore phase bismuth niobate, using magnetic transition metal elements to carry out high entropy design of niobium positions and successfully prepare single-phase samples will have high scientific research value; and by using the high entropy effect, it is very likely to achieve magnetism close to room temperature in this material system, thereby expanding the number of material order parameters, increasing the magnetic order, and ultimately obtaining a new single-phase high entropy ceramic material with both magneto-optical and photoelectric properties. However, there are few reports on related research at present. High-entropy ceramics are usually prepared by solid-phase method, but pyrochlore phase bismuth niobate itself has a complex structure, and it is difficult to form a phase by traditional solid-phase method, and it is very easy to produce Bi5Nb3O 15 The presence of impurities such as BiNbO4 or BiNbO4 makes it difficult to prepare a single phase. Therefore, it is a huge challenge to successfully prepare a single-phase bismuth niobate-based pyrochlore phase high-entropy ceramic. Summary of the invention
[0005] The object of the present invention is to provide a bismuth niobate-based pyrochlore phase high entropy ceramic with magneto-electro-optical multifunctionality and a single-phase preparation method thereof in view of the above-mentioned deficiencies in the prior art. The material can realize the disordered coexistence of multiple magnetic atoms in the bismuth niobate-based pyrochlore phase structure, induce complex magnetic interactions or room-temperature ferromagnetic states, thereby generating new functions such as room-temperature magnetism and room-temperature magneto-dielectric effect.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] The first object of the present invention is to provide a bismuth niobate-based pyrochlore phase high entropy ceramic, the chemical formula of the bismuth niobate-based pyrochlore phase high entropy ceramic is
[0008] (Nb 0.36 Bi 1.64 )(Fe 0.2 Co 0.2 Ni 0.2 Mn 0.2 Cr 0.2 )NbO 7-δ .
[0009] Furthermore, the crystal structure of the bismuth niobate-based pyrochlore phase high entropy ceramic is a defective A2B2O7 type single-phase pyrochlore phase structure, in which some niobium ions occupy the positions of bismuth ions, and five equimolar magnetic transition metal ions occupy the positions of niobium ions and there are a certain proportion of oxygen vacancy defects.
[0010] Furthermore, the bismuth niobate-based pyrochlore phase high entropy ceramic has ferromagnetism and magnetoelectric multiferroic properties at room temperature.
[0011] Furthermore, the bismuth niobate-based pyrochlore phase high entropy ceramic has good broadband light absorption characteristics in the visible-near infrared region of 300nm-2000nm.
[0012] The second object of the present invention is to provide a single-phase preparation method of the above-mentioned bismuth niobate-based pyrochlore phase high entropy ceramic, comprising the following steps:
[0013] S1. Weigh a certain amount of Nb2O5·3H2O amorphous synthetic material containing crystal water and dissolve it in deionized water. Then, add citric acid in an equal molar ratio for complexation. Heat and stir the mixture in a water bath at a certain temperature to dissolve the mixture, and then form a transparent solution A.
[0014] S2, weighing acid-soluble bismuth source compounds, iron source compounds, cobalt source compounds, nickel source compounds, manganese source compounds and chromium source compounds according to the stoichiometric ratio shown in the chemical formula, and dissolving the above components in diluted acid solution, stirring at room temperature to form a clear solution B;
[0015] S3, adding solution A dropwise to solution B, and forming a mixed clear solution C by continuous stirring; adding citric acid and ethylenediaminetetraacetic acid to solution C as complexing agents and combustion aids, and then adding ammonia water dropwise to adjust the pH value to neutral, and finally forming a transparent solution D;
[0016] S4. Transfer solution D to an evaporating crucible, heat it, and allow solution D to undergo sol and gel. After spontaneous combustion, collect the remaining powder to obtain primary powder. Then, grind the collected powder and place it in a muffle furnace for high-temperature pre-sintering and high-temperature sintering to obtain the single-phase high-entropy ceramic block.
[0017] Furthermore, in step S2, the bismuth source compound is bismuth nitrate pentahydrate, the iron source compound is ferric nitrate nonahydrate, the cobalt source compound is cobalt nitrate hexahydrate, the nickel source compound is nickel acetate, the manganese source compound is manganese oxalate, and the chromium source compound is chromium nitrate nonahydrate.
[0018] Furthermore, in step S3, the molar ratio of the added total metal ions, the complexing agent and the combustion improver is 1:1:1, the complexing agent is citric acid, and the combustion improver is ethylenediaminetetraacetic acid.
[0019] Furthermore, in step S4, the high temperature pre-firing temperature is between 500° C. and 800° C., and the heat preservation time is 2 hours.
[0020] Furthermore, the high temperature sintering temperature is between 900 and 1000° C., and the sintering time is between 5 and 7 hours.
[0021] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0022] (1) The bismuth niobate-based pyrochlore phase high-entropy ceramic provided by the present invention has a high-entropy structure designed by using magnetic elements for the B-site high-entropy component in a defective A2B2O7-type bismuth niobate system, and the obtained high-entropy ceramic material still has the characteristics of a single-phase pyrochlore phase structure.
[0023] (2) The bismuth niobate-based pyrochlore phase high entropy ceramic provided by the present invention has positional disorder in its structure, that is, part of the B-site niobium ions occupy the A-site bismuth ion position, and five equimolar magnetic transition metal ions occupy the B-site niobium ion position and a certain proportion of oxygen vacancy defects. Generally, the regular pyrochlore phase structure is a regular arrangement of two sets of lattices of bismuth oxygen tetrahedron and niobium oxygen octahedron, but the positional disorder, multi-type vacancy defects and disordered iron / cobalt / nickel / manganese / chromium oxygen octahedrons will lead to structural distortion and local stacking disorder, and there will be superexchange between neighboring magnetic atoms, which may induce local short-range magnetic order and form a spin glass state or ferromagnetic state; at the same time, there are 3d orbitals of unoccupied electrons in multi-type transition metals, which are easy to hybridize with the 2p orbitals of oxygen atoms, affecting the band structure and thus changing the optical properties.
[0024] (3) The bismuth niobate-based pyrochlore phase high entropy ceramic provided by the present invention exhibits ferromagnetism at room temperature, and also possesses room temperature magnetoelectric multiferroic properties and good broadband light absorption properties in the visible-near infrared 300nm-2000nm region. In addition, it is found that the structure of the ceramic material is very stable, and even after calcination at a high temperature of 1000℃ for 5h, it can still maintain a stable pyrochlore cubic crystal phase structure, and has excellent high temperature resistance.
[0025] (4) The present invention successfully prepares a new type of single-phase high-entropy ceramic material through an improved sol-gel combustion method. The preparation method is simple to operate, energy-saving and efficient, and is easy to promote. At the same time, it can solve the dissolution problem of niobium-based oxides and the problem that traditional solid-phase methods are difficult to form phases.
[0026] (5) The bismuth niobate-based pyrochlore phase high-entropy ceramic provided by the present invention can not only maintain its own dielectric properties and photocatalytic properties, but also newly add room-temperature ferromagnetism and magneto-dielectric coupling, thereby realizing the multifunctionality of the material with both magneto-optical properties. It has a good application prospect in the fields of magneto-electric sensor devices, high-density storage devices, optoelectronic devices, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The XRD patterns of the sample powders in the embodiments and comparative examples and the PDF card comparison with the pyrochlore phase standard samples;
[0028] Figure 2 The cross-sectional SEM images and SEM-EDX spectrum comparison images of the ceramic samples in the embodiments and comparative examples are shown;
[0029] Figure 3These are images of the sample ceramics in Example 1 when sintered at different temperatures;
[0030] Figure 4 It is a comparison diagram of the ZFC-FC magnetization curve and room temperature hysteresis loop corresponding to the samples in the embodiment and the comparative example;
[0031] Figure 5 is the room temperature hysteresis loop diagram of the ceramic sample in Example 1;
[0032] Figure 6 The figure is a comparison diagram of the room temperature ultraviolet visible near infrared diffuse reflectance spectra of the sample powders in the embodiment and the comparative example;
[0033] Figure 7 The magneto-dielectric curve and magneto-dielectric effect versus temperature of the sample ceramic in Example 1 are shown;
[0034] Figure 8 The ON-OFF transient photocurrent density-time curve measured for the electrode made from the sample powder in Example 1. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical scheme and advantages of the present invention clearer, the specific embodiments of the present invention are further described in detail below in conjunction with specific examples and drawings. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.
[0036] Example 1
[0037] This embodiment provides a bismuth niobate-based pyrochlore phase high entropy ceramic.
[0038] (Nb 0.36 Bi 1.64 )(Fe 0.2 Co 0.2 Ni 0.2 Mn 0.2 Cr 0.2 )NbO 7-δ Preparation of powders and blocks.
[0039] (1) Niobium pentoxide containing crystalline water was prepared by conventional methods, and the chemical formula was determined to be Nb2O5·3H2O and an amorphous phase by thermogravimetric method and X-ray phase characterization method. A certain amount of dried and stored amorphous synthetic material containing crystalline water Nb2O5·3H2O was weighed and dissolved in deionized water. In order to dissolve niobium pentoxide containing crystalline water and stably disperse niobium ions in water, citric acid in an equal molar ratio was added for complexation. At the same time, it was necessary to heat the aqueous solution in a water bath on a heating table, keep the temperature of the aqueous solution at about 80°C, and stir it continuously with a magnetic bar. After about 10 minutes, it was completely dissolved to form a clear solution A, which was colorless and transparent.
[0040] (2) According to the amount and stoichiometric ratio of the above-mentioned niobium source, weigh the acid-soluble bismuth source compound, iron source compound, cobalt source compound, nickel source compound, manganese source compound and chromium source compound in turn, and dissolve them in another beaker containing diluted concentrated nitric acid solution. In the embodiment, the compound is preferably: the bismuth source compound is bismuth nitrate pentahydrate, the iron source compound is iron nitrate nonahydrate, the cobalt source compound is cobalt nitrate hexahydrate, the nickel source compound is nickel acetate, the manganese source compound is manganese oxalate, and the chromium source compound is chromium nitrate nonahydrate. Under room temperature, by magnetic stirring, a transparent solution B is finally obtained, and the solution is dark red.
[0041] (3) Then, solution A is added dropwise to solution B using a rubber-tipped dropper, and a mixed clear solution C is formed by continuous stirring. The solution is dark brown. Next, a complexing agent and a combustion aid are added to solution C, and the molar ratio of the added amount is total metal ions: complexing agent: combustion aid = 1:1:1. In the embodiment, the complexing agent and the combustion aid are citric acid and ethylenediaminetetraacetic acid, respectively. The pH value of the above-mentioned mixed solution is neutralized by adding an alkaline solution dropwise to about 7. In the embodiment, the alkaline solution is preferably ammonia water. The above process needs to be stirred until a transparent solution D is formed, and finally a precursor solution is obtained.
[0042] (4) The precursor solution is transferred to an evaporating crucible, and the solution D is heated to pass through sol and gel, and after spontaneous combustion, the remaining powder is collected to obtain a primary powder; the heating is heating on a resistance wire electric furnace. Then, the collected powder is ground and placed in a muffle furnace for high-temperature pre-sintering. The high-temperature pre-sintering temperature is between 500-800°C, preferably 750°C in the embodiment, and the pre-sintering insulation time is 2h. This step is currently used to remove the organic carbon residues mixed in the powder. Too low a temperature cannot volatilize the organic carbon, and too high a temperature easily causes the grains in the powder to fuse and grow, which is not conducive to the volatilization of the organic carbon. The powder remaining after pre-sintering is the single-phase powder of the material described in the present invention.
[0043] (5) The synthesized single-phase powder is formed by a grinding tool and placed in a high-temperature muffle furnace for long-term high-temperature sintering. The high-temperature sintering temperature is 900-1000°C, preferably 950°C in the embodiment, and the sintering time is 5h. After the final high-temperature sintering is completed, the obtained ceramic block is the high-entropy ceramic described in the present invention.
[0044] Comparative Example 1
[0045] This comparative example provides (Nb 0.36 Bi 1.64 )(Fe 1 / 3 Co 1 / 3 Ni 1 / 3 )NbO 7-δ Preparation of ceramic powders and blocks.
[0046] (1) Weigh a certain amount of Nb2O5·3H2O amorphous composite containing crystal water and dissolve it in deionized water, then add citric acid in an equal molar ratio for complexation, and heat and stir in a water bath at a certain temperature to dissolve, thereby forming a transparent solution A';
[0047] (2) weighing bismuth nitrate pentahydrate, iron nitrate nonahydrate, cobalt nitrate hexahydrate and nickel acetate in a stoichiometric ratio respectively and dissolving them in a dilute nitric acid solution, stirring at room temperature to form a clear solution B';
[0048] (3) adding solution A' dropwise to solution B' to form a mixed clear solution C' by continuous stirring; then adding citric acid and ethylenediaminetetraacetic acid in an equal molar ratio of metal ions to solution C', and then adding ammonia water dropwise to neutralize the pH value, finally forming a transparent solution D';
[0049] (4) The solution D' is transferred to an evaporating crucible, and the solution D' is heated to undergo sol and gel, and after spontaneous combustion, the remaining powder is collected to obtain primary powder; then, the collected powder is ground and placed in a muffle furnace for high-temperature pre-sintering at 750°C / 2h to obtain pure material powder; finally, tableting is performed, and high-temperature sintering is performed at 950°C / 5h to finally obtain the ceramic block described in Comparative Example 1.
[0050] Comparative Example 2
[0051] This comparative example provides (Nb 0.36 Bi 1.64 )FeNbO 7-δ Preparation of ceramic powders and blocks.
[0052] (1) Weigh a certain amount of Nb2O5·3H2O amorphous composite containing crystal water and dissolve it in deionized water, then add citric acid in an equal molar ratio for complexation, heat and stir in a water bath at a certain temperature to dissolve, and form a transparent solution A";
[0053] (2) Weighing bismuth nitrate pentahydrate and ferric nitrate nonahydrate in a stoichiometric ratio respectively, dissolving them in a dilute nitric acid solution, and stirring at room temperature to form a clear solution B";
[0054] (3) adding solution A" dropwise to solution B" to form a mixed clear solution C" by continuous stirring. Then, adding citric acid and ethylenediaminetetraacetic acid in an equal molar ratio of metal ions to solution C", and then adding ammonia water dropwise to neutralize the pH value, finally forming a transparent solution D";
[0055] (4) The solution D" is transferred to an evaporating crucible, and the solution D" is heated to undergo sol and gel, and after spontaneous combustion, the remaining powder is collected to obtain primary powder; then, the collected powder is ground and placed in a muffle furnace for high-temperature pre-sintering at 750°C / 2h to obtain pure material powder; finally, tableting is performed, and high-temperature sintering is performed at 950°C / 5h to finally obtain the ceramic block described in Comparative Example 2.
[0056] The ceramics prepared in Example 1, Comparative Example 1 and Comparative Example 2 were respectively subjected to structural characterization, including X-ray diffraction (XRD) and scanning electron microscope energy dispersive spectroscopy (SEM-EDS).
[0057] The relevant testing process is as follows: take 1g of ceramic powder and put it into a special sample slot for XRD test, compact it with a glass sheet, then put the glass sheet with the sample into the XRD measuring instrument, set the relevant parameters, and perform conventional XRD measurement to obtain the XRD spectrum; take the prepared ceramic sheet, break it and stick it on the sample holder of the SEM test with conductive tape, then put it into the SEM instrument to measure the cross-sectional morphology of the ceramic sample, and at the same time collect EDS data at the corresponding position to obtain the SEM-EDS spectrum and the corresponding ceramic cross-sectional microscopic morphology.
[0058] refer to Figure 1 and Figure 2The measured XRD data is completely consistent with the standard PDF#52-1774 corresponding to the pyrochlore phase structure, indicating that no second impurity phase is found in the sample, and confirming that all three samples are single-phase pyrochlore phase structures; compared with the low-entropy ceramic sample, the cross-sectional SEM image of the high-entropy ceramic sample shows that the sample has a good density, indicating that the high-entropy design is beneficial to reduce the porosity and improve the density of the ceramic sample; the measured SEM-EDS spectrum clearly shows that there are five magnetic elements in the high-entropy ceramic sample and the molar ratio is approximately equal, confirming that the actual measured stoichiometric ratio is basically consistent with the theoretical stoichiometric ratio. In addition, the above experimental data also show that the sample structure is still dominated by the interwoven skeleton of bismuth oxygen tetrahedron and niobium oxygen octahedron lattice, suggesting that its structure still has inherent physical properties, such as dielectric properties, photoelectrocatalysis, etc., as well as structural properties, such as high temperature resistance. According to the general range of experimentally measurable oxygen vacancies, the estimated δ range is -0.16 to +0.56.
[0059] refer to Figure 3 In order to verify that the single-phase high-entropy high-temperature ceramic material of the present invention has high-temperature resistance, a high-temperature resistance characteristic is characterized. Specifically, the high-entropy ceramic material is first pressed into a sheet and calcined at 900°C to form a dense ceramic block. The block is then placed in an imaging sintering point tester. By setting the temperature range to 900-1000°C and the heating rate to 1°C / min, a photo is taken to observe the structural changes of the ceramic block during the heating process. The results show that at around 1000°C, the macroscopic structure of the ceramic does not change, and there is no melting or expansion phenomenon. In addition, the XRD spectrum of the sample after the test is also compared with the sample before the test. There is no obvious change, indicating that the prepared ceramic material has high temperature resistance.
[0060] The ceramic samples prepared in Example 1, Comparative Example 1 and Comparative Example 2 were characterized by properties, including magnetic properties, ferroelectric properties, optical absorption spectrum, magneto-dielectric properties, photoelectric effect, etc.
[0061] refer to Figure 4 , Figure 5 and Figure 6 In order to prove that the single-phase high entropy ceramic material of the present invention has good magnetic, ferroelectric and optical properties, the samples were subjected to magnetic measurement, ferroelectric measurement and optical absorption spectrum measurement. These measurements are commonly used in the field of materials science, and the specific measurement process will not be repeated. The magnetic measurement mainly involves temperature measurement and hysteresis loop measurement. The experimental results are shown in Figure 2. Figure 4 The results show that the high entropy material of the present application exhibits good room temperature ferromagnetism, proving that high entropy design of magnetic elements can effectively change and enhance the magnetic properties of bismuth niobate-based materials.
[0062] The ferroelectricity measurement described above specifically uses a ceramic sheet with silver electrodes at both ends to measure the hysteresis loop on a ferroelectric measuring instrument. The experimental results are as follows: Figure 5 The sample shows hysteresis loop characteristics under an electric field of 100 kV / cm at room temperature, confirming that the material has room temperature ferroelectricity. The optical absorption spectrum measurement specifically uses ceramic powder to perform ultraviolet visible near infrared diffuse reflectance spectrum measurement, and the experimental results are shown in Figure 6 As shown, it is determined that the single-phase high-entropy ceramic material has good wide-spectrum light absorption characteristics in the 300nm-2000nm region.
[0063] Furthermore, in order to prove the coupling characteristics of different order parameters inside the single-phase high-entropy ceramic material of the present invention with both magneto-electro-optical multifunctionality, magneto-dielectric effect and photoelectric effect measurements were carried out on the material respectively.
[0064] Magneto-dielectric measurement: First, measure the relationship between the dielectric constant and temperature from 50K to 340K under zero magnetic field, and then repeat the measurement of the relationship between the dielectric constant and temperature from 50K to 340K under 1 Tesla. The part where the two curves do not overlap indicates the magneto-dielectric effect. The experimental results are as follows: Figure 7 As shown. The results show that after the magnetic structure changes, the effect of the magnetic field on the dielectric constant is more obvious, and the heating and cooling curves do not overlap after the magnetic transition, indicating that there is a magnetic thermal hysteresis phenomenon near room temperature; further, low temperature mainly shows ferromagnetism, and a magnetic transition occurs near 200K. Above 200K, the magnetism is more complex and there are obvious interactions between different magnetic structures, so that complex magnetic interactions are more likely to induce changes in the dielectric constant. Through the measurement of the magnetic dielectric coefficient, it can be obtained that the area with a more obvious magnetic dielectric effect is the temperature area above 200K, and the magnetic dielectric coefficient can reach more than 3%, especially covering the room temperature range.
[0065] Photoelectric effect measurement: The ceramic powder of the present application is made into a photoelectrode of a certain area on a FTO conductive substrate, and then the ON-OFF transient photocurrent Jt curve is measured by the three-electrode method in a neutral sodium sulfate solution. The experimental results are as follows Figure 8 As shown, the results prove the existence of light-induced current, that is, the material has a photoelectric effect.
[0066] The above-mentioned structure and performance characterization experimental results show that the high-entropy high-temperature ceramic material prepared by the present invention also has a pyrochlore phase structure and is a single-phase material. It fully proves that the preparation method provided by the present invention can successfully prepare a single-phase high-entropy ceramic material, which has great scientific research value. The single-phase high-entropy material of the present invention can show room temperature ferromagnetism, room temperature ferroelectricity, good light absorption characteristics in a wide range of visible-near infrared, and possesses magneto-dielectric effect and photoelectric effect, etc., indicating that it has magneto-photoelectric multifunctional characteristics, and there is a coupling effect between order parameters. In addition, the experimental data of the above-mentioned comparative sample show that chemical components doped with a small amount of magnetic elements cannot well display room temperature ferromagnetism and excellent light absorption characteristics, which fully proves that the high-entropy structure design of magnetic elements involved in the present invention can bring about the particularity and superiority of material performance.
[0067] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.
[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A bismuth niobate-based pyrochlore phase high entropy ceramic, characterized in that: The chemical formula of the bismuth niobate-based pyrochlore phase high entropy ceramic is (Nb 0.36 Bi 1.64 )(Fe 0.2 Co 0.2 Ni 0.2 Mn 0.2 Cr 0.2 )NbO 7-δ .
2. The bismuth niobate-based pyrochlore phase high entropy ceramic according to claim 1, characterized in that: By using magnetic transition metal elements for high entropy design at the niobium ion position, the resulting crystal structure is still a defective A2B2O7 type single-phase pyrochlore phase structure. Some niobium ions in the structure occupy the bismuth ion position, and five equimolar magnetic transition metal ions occupy the B-site niobium ion position.
3. The bismuth niobate-based pyrochlore phase high entropy ceramic according to claim 1, characterized in that: The bismuth niobate-based pyrochlore phase high entropy ceramic has ferromagnetism at room temperature.
4. The bismuth niobate-based pyrochlore phase high entropy ceramic according to claim 1, characterized in that: The bismuth niobate-based pyrochlore phase high entropy ceramic has both ferromagnetism and ferroelectricity at room temperature, that is, has room temperature magnetoelectric multiferroicity.
5. The bismuth niobate-based pyrochlore phase high entropy ceramic according to claim 1, characterized in that: The bismuth niobate-based pyrochlore phase high-entropy ceramic has good broadband light absorption characteristics in the visible-near infrared 300nm-2000nm region.
6. The single-phase preparation method of bismuth niobate-based pyrochlore phase high entropy ceramics according to any one of claims 1 to 5, characterized in that The synthesis is carried out by dissolution and sol-gel combustion method, which specifically includes the following steps: S1. Weigh a certain amount of Nb2O5·3H2O amorphous synthetic material containing crystal water and dissolve it in deionized water. Then, add citric acid in an equal molar ratio for complexation. Heat and stir the mixture in a water bath at a certain temperature to dissolve the mixture, and then form a transparent solution A. S2, weighing acid-soluble bismuth source compounds, iron source compounds, cobalt source compounds, nickel source compounds, manganese source compounds and chromium source compounds according to the stoichiometric ratio shown in the chemical formula, and dissolving the above components in diluted acid solution, stirring at room temperature to form a clear solution B; S3, adding solution A dropwise to solution B, and forming a mixed clear solution C by continuous stirring; adding citric acid and ethylenediaminetetraacetic acid to solution C as complexing agents and combustion aids, and then adding ammonia water dropwise to adjust the pH value to neutral, and finally forming a transparent solution D; S4. Transfer solution D to an evaporating crucible, heat it, and allow solution D to undergo sol and gel, and then spontaneously combust. Then, collect the remaining powder to obtain primary powder. Then, grind the collected powder, and place it in a muffle furnace for high-temperature pre-firing and high-temperature sintering to obtain the single-phase high-entropy ceramic block.
7. The preparation method according to claim 6, characterized in that: In step S2, the bismuth source compound is bismuth nitrate pentahydrate, the iron source compound is ferric nitrate nonahydrate, the cobalt source compound is cobalt nitrate hexahydrate, the nickel source compound is nickel acetate, the manganese source compound is manganese oxalate, and the chromium source compound is chromium nitrate nonahydrate.
8. The preparation method according to claim 6, characterized in that: In step S3, the molar ratio of the added total metal ions, the complexing agent and the combustion improver is 1:1:1, the complexing agent is citric acid, and the combustion improver is ethylenediaminetetraacetic acid.
9. The preparation method according to claim 6, characterized in that: In step S4, the high temperature pre-firing temperature is 500-800° C., and the heat preservation time is 2 hours.
10. The preparation method according to claim 6, characterized in that: In step S4, the high temperature sintering temperature is 900-1000° C., and the sintering time is 5-7 hours.
Citation Information
Patent Citations
Bismuth-based pyrochlore dielectric energy storage ceramic and preparation method thereof
CN114988873A
Medium-entropy ceramic material with high energy storage density and high energy storage efficiency and preparation method thereof
CN116023131A
Sodium bismuth titanate-based high-entropy ceramic material with high energy storage characteristic as well as preparation method and application of sodium bismuth titanate-based high-entropy ceramic material
CN116082034A
High-entropy calcium bismuth niobate-based lead-free piezoelectric ceramic material and preparation method thereof
CN117586008A
High-entropy niobate ceramic material applied to high-temperature thermal protection and preparation method of high-entropy niobate ceramic material
CN118026678A